Frick՚s Legal and Political Views - Aleksanyan, Alvard (Bulletin of Yerevan University C: Jurisprudence, 2024)
Frick (1230-1310) is one of the talented and original representatives of medieval Armenian secular poetry. He remained in history as a poet, but it is worth noting that in his few works that have come down to us, he turned to multifaceted legal, political, and religious issues. He was a consistent successor and developer of the medieval literary secular-democratic trend. Not being free from medieval religious ideology, he introduced criticism and analysis into the idealistic worldview. One of the themes of his secular poems is the historical fate of the Armenian people, the political, economic and legal status of the impoverished population of Armenia in the 13th century during the reign of the Mongol-Tatar yoke. He expressed his protest against the reigning lawlessness, inequality and injustice. He expressed confidence that there would be political changes and the end of the Tatar kingdom. He believed that in the Christian world there will be freedom, peace and equality, which is possible only with the transformation of political power. Among Christians, he was looking for a king who would come to the aid of Christians who were being tortured and killed by the lawless. Along with national-political problems, Frick also touched upon socio-economic, class, and universal problems. He very early noticed the existing injustices and inequalities in society, the social stratification of society into two opposite classes: the rich and the poor, which he explained not by divine providence, but by social relations. He expressed the ideas of class equality and free expression of the will of people. Frick in his poems and instructions condemned the public and private bad manners of that time and established, in the form of prohibitions and instructions, the norms of behavior and lifestyle for all sections of the Armenian society.